Surviving science: coping with exit-decisions in physics and history - Fenkner, Tim; Gottschalk-Rayling, Jonas (Minerva, 2024)
Academic careers between the completion of a PhD and the acquisition of tenure are characterized by short term contracts, high levels of competition, and future uncertainty. Existing research indicates that uncertainty is a primary cause for postdocs in all disciplines to constantly question the continuation of their career. Despite this commonality between disciplines, we argue that future imaginations, coping strategies and ultimately the decision-making practices to exit or remain in academia differ in each discipline. Drawing from 60 qualitative interviews with physicists and historians, we compared imaginations of the labor market inside and outside of academia, as well as narratives on how they perceive their agency to exit or remain. Our data shows that imaginations of the labor market outside of academia, have considerable consequences for their sense of precarity and planning of career paths. We propose that the uniform concept of future uncertainty must be separated into ‘existential uncertainty’ and ‘secured uncertainty’, which more accurately reflect the problems postdocs are confronted with and the resulting coping strategies. While those who consider their uncertainty as existential either evoke narratives of survival to continue in adverse conditions or begin parallel careers as added security. Those who perceive their future as uncertain but generally secured rely either on their ability to decide when necessary or postpone the question indefinitely. These differences that correlate with our chosen disciplines have important implications for research quality as well as mental-health hazards and further our understanding of self-exploitation and precarity in academia.
Gesehen am 09.04.2025